Penerapan Limit Fungsi untuk Mencari Keuntungan Maksimum Ditinjau dari Biaya Marginal - Sinta Fitriyani; Nanda Anugrah; Dedek Kustiawati; Wulan Mutiara Cahyani (Publikasi Indonesia, 2022)
Marginal costs are changes in total costs in the form of increases or decreases in total costs due to changes in the quality of goods or services. Through the types of production costs used as processing costs, it will be seen to what extent the use of capital will be used and profits will be obtained. This analysis will help to what extent a company can determine the planning for the business that is built, whether to get maximum or minimum profits. This study uses literature study, which is research in which data sources and data collection are obtained by taking library data, reading, recording and processing the data as research material. Based on an analysis of literature data regarding